PROXIMATE ANALYSIS, CRUDE FIBER, AND AMINO ACID PROFILE OF SEAWEED CRACKERS (EUCHEUMA COTTONI) FORTIFIED WITH YELLOWFIN TUNA (THUNNUS ALBACARES) BONE AND SKIN FLOUR - Arwita Irawati; Zazkia Nurul Izzyah; Asjun Asjun (INASUA: Jurnal Teknologi Hasil Perikanan, 2026)
Seaweed crackers based on Eucheuma cottoni are potential functional food products when fortified with protein- and mineral-rich ingredients. This study aimed to analyze the proximate composition, crude fiber content, and amino acid profile of seaweed crackers fortified with yellowfin tuna (Thunnus albacares) bone and skin flour at various concentrations. A completely randomized design (CRD) was applied with five treatment levels of tuna bone and skin flour: F1 (0%), F2 (5%), F3 (10%), F4 (15%), and F5 (20%), each with three replications. Proximate analysis followed AOAC (2016) methods covering moisture, ash, fat, protein, crude fiber, and carbohydrate content. The amino acid profile of the selected treatment was analyzed by HPLC (IK.LP-04.7-LT-1.0 method). Results showed that fortification significantly affected (p<0.05) all proximate parameters. The selected treatment F4 (15%) had moisture 5.03%; ash 7,72%; crude fat 17.00%; crude protein 0.63%; crude fiber 10.70%; and carbohydrate 58.91%. Amino acid profile of F4 showed total amino acids of 10,88% (w/w), with glutamate as the highest (2.74%), followed by glycine (1.96%) and arginine (1.13%). The presence of eight complete essential amino acids makes these fortified seaweed crackers a high-nutritional-value functional food.